NGSS-oriented chemistry test instruments: Validity and reliability analysis with the Rasch model - Lia, Roudloh Muna; Rusilowati, Ani; Isnaeni, Wiwi (REID (Research and Evaluation in Education), 2020)
The instrument of measuring test attributes must be valid and reliable. This study was carried out since the validity and reliability testing of the chemistry items used by the testee is necessary. This study aims to estimate the validity and determine the reliability of chemical test instruments oriented Next Generation Science Standards (NGSS). The research was conducted through a quantitative descriptive approach in two vocational schools of engineering program which had 130 testees. The instrument used was an NGSS-oriented chemistry test instrument containing 35 items and an expert validation questionnaire. The obtained test participant’s response from the test instrument was collected through the documentation method. Item in NGSS test were presented to three subject matters experts. The validities used were the content validity and the construct validity. The reliability was tested through internal consistency and interrater consistency approaches. The results show that content validity (Aiken’s V) is at a range of 0.50 to 1.00. The value of the unexplained variance is less than 10%, which means that it is well-categorized. This analysis is strengthened by CFA which has a goodness of fit and a good measurement model fit. The parameters used to test model fit are CFI, NFI, RMSEA and the value of loading factor. Some results values are over 0.90 and RMSEA is 0.00 and more than 0.3 of loading factor value on each item. All scales had alpha reliability more than the criteria of 0.70. Thus, the developed chemical test item were proven as valid and reliable instruments.